Modulating the electron-transfer properties of a mixed-valence system through host–guest chemistry. Issue 2 (5th December 2014) - Zubi, Ahmed; Wragg, Ashley; Turega, Simon; Adams, Harry; Costa, Paulo J.; Félix, Vítor; Thomas, Jim A.
Abstract : Herein, we report that the interplay between the binding properties and redox activity of a self-assembled trinuclear Ru II macrocycle leads to an hitherto unreported phenomenon, in which access to specific MV states is gated by host–guest chemistry. Abstract : Metal directed self-assembly has become a much-studied route towards complex molecular architectures. Although studies on mixed valence, MV, systems accessible through this approach are almost non-existent, the potential applications of such systems are very exciting as MV states provide the basis of a number of molecular-scale devices, including single electron wires and switches. Furthermore, while many novel hosts for guest ions and molecules have been developed through metal directed self-assembly, as these products tend to be kinetically labile, very few electrochemical studies have been reported. Herein, we report that the interplay between the binding properties and redox activity of a self-assembled trinuclear Ru II macrocycle leads to an hitherto unreported phenomenon, in which access to specific MV states can be gated by host–guest chemistry. Thus, this system is the first in which MV states and the extent of electron delocalisation are switched by an ion without any change in electrochemical potential.